Integration of Practical Work into Teaching and Learning of Physics at the Senior High School Level: Integration of Practical Work into Teaching and Learning of Physics at the Senior High School Level - Asamoah, Donusem Yao; Aboagye, Godwin Kwame (The Oguaa Educator, 2019)
Practical work forms an integral part of teaching and learning as enshrined in the teaching physics syllabus designed for senior high schools in Ghana. This presupposes that the final grade of students is influenced by their performance in physics practical work. Hence, practical work in physics needs to be utilised to improve students’ performance. This study, therefore, sought to examine how practical work is integrated into the teaching and learning of physics at the senior high school level in the Volta Region of Ghana. In all, 16 physics teachers and 212 science students randomly sampled took part in the study. It was found that though teachers accept practical work as an essential ingredient for students’ understanding of concepts, they are not up-to-date on how practical work should be integrated into the teaching and learning of physics as prescribed by the syllabus for physics. Also, the teaching of practical work is done via group work, hands-on activity, interactive demonstrations, discussion and lecture. It is recommended that teachers should adopt integrating practical work into lessons instead of separating them from theory.